DIELECTRIC PROPERTIESOF SMECTIC-Cα* PHASE - Andika Fajar; Hiroshi Orihara (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2006)
DIELECTRIC PROPERTIESOF SMECTIC-Cα* PHASE. Linear and third-order nonlinear dielectric measurements have been performed within the smectic-Cα* phase of antiferroelectric liquid crystal 4-(1-methyl-heptyloxycarbonyl) phenyl 4-octylcarbonyloxybiphenyl-4-carboxylate (MHPOCBC). In the low temperature region of smectic-Cα* phase, we observed the hysteresis of dielectric constant in cooling and heating process measurement. From the frequency dispersion measurement, it has been found that the frequency relaxation of antiferroelectric Goldstone mode and ‘low frequency mode’, decreased with increasing the temperature until approach the center of the smectic-Cα* phase.